Safety and tolerability of extended-release acetylsalicylic acid capsules: a summary of double-blind comparative studies. (November 2016) - Patrick, Jeff; Johnson, Andrew; Dillaha, Larry; Pennell, Andrew T
Aim: To evaluate tolerability of a new extended-release acetylsalicylic acid (ER-ASA).Materials & methods: Daily ER-ASA (162.5–1300 mg) for up to 6 weeks was evaluated (four studies; n = 565). Safety of ER-ASA, immediate-release (IR; 150–1200 mg) ASA and enteric-coated ASA (75 mg) was assessed.Results: Forty-three out of 184 (23.4%) patients with atherosclerosis (ER-ASA 162.5 mg group) experienced adverse events versus 51/195 (26.2%) patients receiving IR-ASA 150 mg. Overall, 48.7 and 51.3% of patients in the ER-ASA group experienced no gastrointestinal discomfort or any gastrointestinal symptoms, respectively, versus 42.1 and 57.9% of patients in the IR-ASA group, respectively. In healthy volunteers, adverse event incidence was comparable between ER-ASA and IR-ASA and between ER-ASA and enteric-coated ASA.Conclusion: Safety of the new ER-ASA formulation was consistent with other ASA formulations.